2012
DOI: 10.1103/physrevd.85.014030
|View full text |Cite
|
Sign up to set email alerts
|

Very light axigluons and the top asymmetry

Abstract: We show that very light (50 -90 GeV) axigluons with flavor-universal couplings of order g s /3 may explain the anomalous top forward-backward asymmetry reported by both CDF and D0 collaborations. The model is naturally consistent with the observed tt invariant mass distribution and evades bounds from light Higgs searches, LEP event shapes, and hadronic observables at the Z pole. Very light axigluons can appear as resonances in multijet events, but searches require sensitivity to masses below current limits.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 85 publications
1
21
0
Order By: Relevance
“…If either the couplings to the light quarks or to the top quark are axial, the interference with the SM is identically zero. If the resonance is within kinematical reach, it will show up anyway, unless it is very wide [27][28][29][30] or below threshold [30,31]. On the other hand, models with t-channel exchange of new particles lead to departures at the high-mass tail [32][33][34].…”
Section: Jhep08(2014)172mentioning
confidence: 99%
“…If either the couplings to the light quarks or to the top quark are axial, the interference with the SM is identically zero. If the resonance is within kinematical reach, it will show up anyway, unless it is very wide [27][28][29][30] or below threshold [30,31]. On the other hand, models with t-channel exchange of new particles lead to departures at the high-mass tail [32][33][34].…”
Section: Jhep08(2014)172mentioning
confidence: 99%
“…[44] it was shown that the deviation from the SM prediction to the measured Tevatron top forward-backward asymmetry could also be due to light axigluons. This idea has been discussed in different scenarios for axigluons with masses in the range of 50 − 1000 GeV [45][46][47][48][49], and usually with a large axigluon decay width to prevent strong bounds from measurements of tt invariant mass spectra. Extensive studies of the phenomenology of light axigluons have been performed, including [50][51][52][53][54][55][56][57][58][59].…”
Section: Jhep09(2014)084mentioning
confidence: 99%
“…Although QCD and QED can do so, it is known that the majority of new physics models need some flavor structure for the positive asymmetry. The only known possible new physics model without flavor structure is light axigluons [56][57][58][59]. Thus, the possibility of flavorless model building is thought exciting.…”
Section: Rg-induction Of Top Asymmetriesmentioning
confidence: 99%